A Mysterious Role of Arginine Vasopressin Levels in Ménière's Disease—Meta-analysis of Clinical Studies. Issue 2 (February 2017) - Wu, Jing; Zhou, Jie; Dong, Lu; Fan, Wenjing; Zhang, Jinyu; Wu, Caiqin
Abstract : Objective: There are contradicting claims that patients with Ménière's disease (MD) have elevated levels of arginine vasopressin (AVP). The results of published studies regarding the difference of AVP level between MD patients and non-MD control subjects are inconsistent. We propose that the discrepancy of AVP levels during different MD phases may be a potential reason. Thus, we conducted a meta-analysis to analyze the precise estimate of this hypothesis. Data Sources: PubMed, Medline, and Cochrane databases from the earliest publication, up until September 2016; references from meta-analyses and related review articles. Study Selection and Data Extraction: Clinical studies that reported AVP level in MD patients and non-MD controls were independently reviewed according to the inclusion criteria. The Newcastle–Ottawa Scale was used to assess quality of studies. Data Synthesis: Random effects model was used to calculate the weighted mean difference. Conclusion: Eight studies met the inclusion criteria. AVP levels of MD patients in acute phase (WMD = 2.29, 95% CI = 0.84–3.74, Z  = 3.10, p  = 0.002) were significantly higher than non-MD subjects. For MD patients in remission phase the difference of AVP levels between the MD patients and the non-MD controls was found (WMD = 0.54, 95% CI = −0.06 to 1.02, Z  = 2.20, p  = 0.03). However, AVP level was not an ideal biomarker of MD patients. Regardless of MD phase, there were no significant differences in the AVP level of MD patients (WMD = 0.27, 95% CI = −0.10 to 0.64, Z  = 1.43, p  = 0.15). Future investigations with larger sample sizes are needed to verify the results.